2015
DOI: 10.1186/s40200-015-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on glycemic control in patients with type 2 diabetes: a systematic review of interventional studies

Abstract: BackgroundDiabetes and vitamin D deficiency are global epidemics. Researchers have long been exploring the role of potentially modifiable factors to manage type 2 diabetes. We conducted a systematic review of prospective studies and randomized controlled trials that involved vitamin D supplementation and specifically intended to study glycemic outcomes related to type 2 diabetes.MethodsTwo authors independently searched Medline and PubMed for longitudinal studies that had assessed the effect of vitamin D suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 50 publications
3
37
0
1
Order By: Relevance
“…[48][49][50][51][52][53][54][55] In recent meta-analyses and systematic reviews, this led to the notion that there is currently no evidence to support a routine correction of vitamin D insufficiency in patients with diabetes mellitus or glucose intolerance. 7,8,18,19,56,57 Nevertheless, the heterogeneity between the different trials, especially with regard to dose, treatment duration and ethnicity, leaves the possibility that there are certain subgroups of patients who might benefit from vitamin D supplementation. 7,8,18,19,56,57 The present findings, if confirmed in other larger trials, may help to define subgroups of patients who might benefit from vitamin D supplementation with regard to control of glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50][51][52][53][54][55] In recent meta-analyses and systematic reviews, this led to the notion that there is currently no evidence to support a routine correction of vitamin D insufficiency in patients with diabetes mellitus or glucose intolerance. 7,8,18,19,56,57 Nevertheless, the heterogeneity between the different trials, especially with regard to dose, treatment duration and ethnicity, leaves the possibility that there are certain subgroups of patients who might benefit from vitamin D supplementation. 7,8,18,19,56,57 The present findings, if confirmed in other larger trials, may help to define subgroups of patients who might benefit from vitamin D supplementation with regard to control of glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,18,19,56,57 Nevertheless, the heterogeneity between the different trials, especially with regard to dose, treatment duration and ethnicity, leaves the possibility that there are certain subgroups of patients who might benefit from vitamin D supplementation. 7,8,18,19,56,57 The present findings, if confirmed in other larger trials, may help to define subgroups of patients who might benefit from vitamin D supplementation with regard to control of glucose homeostasis. Mechanistic evidence has shown that vitamin D is required for normal phase 1 and 2 insulin responses to hyperglycaemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the optimal vitamin D dosing protocol in terms of concentration and frequency is unclear . This is a consistent technical problem in study design, as many interventional studies that are grounded in epidemiological evidence suggesting low vitamin D is associated with an outcome, show no effect for vitamin D supplementation . However, attempts to overcome this with high‐dose vitamin D supplementation may be harmful .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have reported glycemic benefits and improvements in beta cell function among vitamin D deficient adults upon vitamin D supplementation. 11,12 Since the previously published reviews on this topic, 8,9 we found 11 additional eligible studies; by updating the search and using a more comprehensive set of search terms compared to the prior reviews, we found six new RCTs completed since the previous review and five older studies not included in previous systematic reviews that met the inclusion criteria in our review.…”
Section: Introductionmentioning
confidence: 99%